Picturing the reader : reading and representation in the long nineteenth century - Palmer, Beth; Palmer, Beth; Yeates, Amelia; Yeates, Amelia (Writing and culture in the long nineteenth century, 2022)
"The long nineteenth century saw a prolific increase in the number of books being produced and read and, consequently, in the number of visual and textual discourses about reading. This collection examines a range of visual and textual iconographies of readers produced during this period and maps the ways in which such representations engaged with crucial issues of the period, including literary value, gender formation, familial relationships, the pursuit of leisure and the understanding of new technologies. Gauging the ways in which Victorians conceptualised reading has often relied on textual sources, but here we recognise and elaborate the importance of visual culture - often in dialogue with textual evidence - in shaping the way people read and thought about reading. This book brings together historians, literary scholars and art historians using a range of methodologies and theoretical approaches to address ideas of readership found in fine art, photography, arts and craft, illustration, novels, diaries and essays. The volume shows how the field of readership studies can be enriched and furthered through an interdisciplinary approach and, in particular, through an exploration of the visual iconography of readers and reading"--